(untitled) (Nigerian Journal of Technology, 2012)
Tin-Lead solder has been the standard joining material for use in electronic, chemical, automotive and other industries until various regulations around the world began to limit the use of lead due to its toxic effects. In this work, some lead – free solder alloys were produced and characterized for possible replacement of Tin-Lead solders. The solder alloys produced are: 91Sn–9Zn, 60Sn–40Zn, 42Sn–58Bi, and 90Sn–10Bi. Tin–lead solder alloy was also produced and subjected to the same wettability test with the other alloys under the same conditions for the purpose of comparing results. A characteristic of lead–free solders that greatly affects its solderability is its ability to wet the materials it joins. Based on this, a wettability test using copper grid was conducted on the solder alloys produced. The result shows that wetting time varied from 4 seconds to 5 seconds for the lead-free solders while it was 4.7 seconds for the Tin-Lead solder. Also wetting area ranged from 5.8% to 8.9% for the lead-free alloys and 8.3% for the lead containing solder. The respective contact angles in degrees for the lead-free solders varied from 580 - 730, while that for the lead solder was 570.